1997
DOI: 10.1093/oxfordjournals.eurheartj.a015175
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of treatment of atrial fibrillation with low-energy intracardiac cardioversion and conventional external cardioversion

Abstract: Internal cardioversion is effective in restoring sinus rhythm. It might be indicated in patients in whom external cardioversion had failed or in whom external cardioversion is assumed to be difficult or even contraindicated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
58
1
3

Year Published

2000
2000
2007
2007

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(63 citation statements)
references
References 0 publications
1
58
1
3
Order By: Relevance
“…The rate of SR maintenance after low-energy ICV has varied from 32% to 71% at 6 to 15 months. 6,7,9,13,14,17,[19][20][21][22][23] The variation in these numbers is due to the different types of antiarrhythmic drugs utilized and the different patient populations studied. Our 23% rate of SR at 18 months in the ICV group is lower than these figures.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The rate of SR maintenance after low-energy ICV has varied from 32% to 71% at 6 to 15 months. 6,7,9,13,14,17,[19][20][21][22][23] The variation in these numbers is due to the different types of antiarrhythmic drugs utilized and the different patient populations studied. Our 23% rate of SR at 18 months in the ICV group is lower than these figures.…”
Section: Discussionmentioning
confidence: 99%
“…25) The only trial that compared low-energy ICV to TT CV in a prospective fashion included 187 patients with chronic AF. 9) It is important to note that this trial was not randomized and the initial CV modality was left to the patient's choice and crossover to the alternative strategy was allowed in case of CV failure with the initial strategy. The acute success was significantly greater with the ICV modality (93% versus 79%, P < 0.05).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The method has been proven to be safe and of benefit with respect to primary success rate and long-term effects. [3][4][5][6] The introduction of new therapeutic approaches in the treatment of patients is generally justified by greater efficiency and Clin. Cardiol.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Antiarrhythmic drugs and curative surgical and ablative therapies are still of limited efficacy, and their incidence of adverse effects is not insignificant. [3][4][5] Because cardioversion with intrathoracic electrodes is more efficacious than transthoracic defibrillation 6 and the implantable atrial defibrillator has been shown to be feasible, 7 many recent investigations have focused on minimizing the energy requirements of internal cardioversion through novel waveforms or electrode configurations. 8 -12 Still, the most efficient cardioversion strategy clinically used, with biphasic waveforms and lead systems in which shock fields encompass both atria, requires shock strengths that are not sufficiently low to be tolerated by most patients without sedation.…”
mentioning
confidence: 99%